EXPERIMENTAL STUDY ON THE REDUCTION OF CHROMIUM (VI) TO CHROMIUM (III) USING CAMU CAMU - Rivera C., D. (2010)
Laboratory tests were done to determine the reducing effect of ascorbic acid, citric acid and camu camu (Myrciana dubia). Tests with ascorbic acid and citric acid were made using 2, 3.5 and 7 equivalents of acid to 100 rpm and initial pH of 10. The content of ascorbic and citric acid was determined at 2 and 1.9 grams, respectively, per 100 grams of fresh fruit camu camu. The results indicate that ascorbic acid reduces chromium (Vi) up to 98% in 90 seconds. Citric acid shows no activity.